Selection of the best Pre-Diploma science student using a fuzzy approach / Mazalan Sarahintu, Zamali Tarmudi and Ajis Lepit - Sarahintu, Mazalan; Tarmudi, Zamali; Lepit, Ajis (2017)
Evaluating students' academic performance using appropriate techniques is crucial to ensure a fair assessment of their qualities. This paper proposes a fuzzy logic method for specifically selecting the best pre-diploma science student in Universiti Teknologi MARA (UiTM) Cawangan Sabah. The method considers not only academic achievement, but also soft skills and other abilities in the evaluation process. A case study, was conducted based on the results of the students of the November 2013 - March 2014 intake. It was found that our proposed approach had the unique advantage of clearly distinguishing every single score obtained by the students. Also. the results showed that the approach is highly beneficial for problem-solving under uncertainty data sets environment.